Archaeological indicators of working organization during the “La Unión” phase (700-1100 CE) at Nuevo Corinto site: a lithic evidence study - Sanabria, Silvia (2018)
This study analyzes the lithic evidence recovered from a number of different contexts within the excavation of Nuevo Corinto in the archaeological sub-region of the Costa Rican Caribbean. This research examines lithic material culture with the goal of providing a better knowledge of labor organization during La Union phase (CE 700-1100). The determination of the context in which each sample was found and the technological analysis of both artefacts and debitage are key elements to understand how lithic production was organized. However, the complex socio-political structure of settlements like Nuevo Corinto must be also taken into account. At least four elements from different consumption and production contexts suggest that the community of Nuevo Corinto was able to produce all the lithic artefacts necessary to the preservation of its social order.